2021
DOI: 10.1186/s13046-021-02073-8
|View full text |Cite
|
Sign up to set email alerts
|

Neuromedin U induces an invasive phenotype in CRC cells expressing the NMUR2 receptor

Abstract: Background Successful colorectal cancer (CRC) therapy often depends on the accurate identification of primary tumours with invasive potential. There is still a lack of identified pathological factors associated with disease recurrence that could help in making treatment decisions. Neuromedin U (NMU) is a secretory neuropeptide that was first isolated from the porcine spinal cord, and it has emerged as a novel factor involved in the tumorigenesis and/or metastasis of many types of cancers. Previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…In the ENAS condition we found upregulation of NMU, EREG and SNHG12 genes. NMU and EREG encode for Neuromedin U and Epiregulin, respectively, both of which are involved in tumor invasion and progression ( 50, 51 ). SNHG12 encodes for a long non-coding RNA, which can regulate tumor cell invasion and metastases in endometrial cancer ( 52 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the ENAS condition we found upregulation of NMU, EREG and SNHG12 genes. NMU and EREG encode for Neuromedin U and Epiregulin, respectively, both of which are involved in tumor invasion and progression ( 50, 51 ). SNHG12 encodes for a long non-coding RNA, which can regulate tumor cell invasion and metastases in endometrial cancer ( 52 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, in bladder cancer ( 46 ), endometrial carcinoma ( 47 , 48 ) and breast cancer ( 49 ), lung adenocarcinoma ( 50 ), NMU overexpression can promote tumor cell growth, enhance tumor formation and metastasis, and increase tumor drug resistance. The latest study found for the first time that NMUR2 activation promoted signaling in colorectal cancer (CRC) cells, and that NMU improves the mobility and invasiveness of NMUR2-positive CRC cells ( 51 ). The specific mechanisms behind these differing effects are not clear, but may be related to the tumor type, positive, and negative regulation of oncogenes, and the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…NMU expression has been found to be elevated in various cancers, including hepatocellular cancer, pancreatic cancer, and colorectal cancer (CRC) 23,24,29 . It has been reported that NMU accelerates the migration and invasion of CRC cells by activating ERK1/2 kinases 23 .…”
Section: Discussionmentioning
confidence: 99%
“…NMU expression has been found to be elevated in various cancers, including hepatocellular cancer, pancreatic cancer, and colorectal cancer (CRC) 23,24,29 . It has been reported that NMU accelerates the migration and invasion of CRC cells by activating ERK1/2 kinases 23 . In this study, we hypothesized that NMU might promote malignant PTC progression through E2F targets, G2M checkpoints, epithelialmesenchymal transition, the IL6/JAK/STAT3 signaling pathway, the KRAS signaling pathway, and the IL2/STAT5 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation